Autonomous Solar Panels Dry Cleaning System for Dust Removal using Microcontroller and Sensors - Ir. Dr. Dhaksyani Ratnadurai, Lim Chong Jin, Rosli Yusop (International Journal of Advanced Science and Technology, 2020)
The aim of thisprojectis to design an autonomoussolar panels cleaning system for improvingthe power output of solar panels by removingaccumulateddust on the glass surface of panels. In thisproject, the dustdetectionmechanismwasdesignedusing voltage, current, LDR and IR sensor. Then, the sensors’ data wasacquired and processed by the Arduino microcontroller to actuate an autonomouscleaning process thatclearsawaydustfrom the panel’s surface. The data wasalsopublished to ThingSpeak and Blynk server for monitoring purposesusingthe Internet of Things (IoT) technology. The performance of the developed system wasevaluated by power output test, cycle time test, high loadings test, dustparticle sizes test and weather conditions test. It wasobservedthat the proposed system hada relatively high accuracy of 88.03% to 99.47% as compared to the existingsystems. On average, the cycle time of the cleaning process on a flat surface and inclinedwere 31.9 seconds and 32.3 seconds respectively. In the cleaning performance test, itwasinferredthat the proposed system was capable of clearing high loadings of dust and 25µm dustparticleswith an averageaccuracy of 93.4% and 95.5% relatively. However, the system hadcleaningefficiency as low as 71.5% whencleaning on rainyweather as compared to the averagecleaningefficiency of 96.1% on a dry sunnyday.